The Development of Raya-In: Learning Media Based on Smart Apps Creator to Improve Primary School Social Science Learning - Nurul Hidayah; Petra Kristi Mulyani (Postgraduate, University of Mataram, 2024)
Technology-based learning media in social science are not readily available in primary schools. Meanwhile, learning media, especially technology-based, supports social science competencies for primary school students. This study aimed to develop learning media, named Raya-In (Ragam Budaya Indonesia), based on Smart Apps Creator to improve the social science learning of fourth-grade students in SDN Kangkung 01 within the Indonesian cultural diversity theme. This study used the Borg and Gall model design, which consisted of 8 stages: potential and problem analysis, data collection, product design, product validation, revision, small-scale trial, large-scale trial, and final product. The study involved media experts and content experts to validate the media. The subjects were fourth-grade students of SDN Kangkung 1 (n=39). Data was collected by observation, interview, pretest, questionnaire, documentation, and posttest. The final result showed that Raya-In passed the media and content experts' evaluation and revision processes. The media and content experts gave high scores in the qualified category. The Pretest, posttest, T-test, and N-gain tests showed that Raya-In supported social science learning. The study aligned with learning in the current era, using technology-based media. Raya-In development based on Smart Apps Creator was validated to support social science learning in primary school.